UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V MUATAN IPA MENGGUNAKAN MODEL KOOPERATIF NUMBERED HEAD TOGETHER (NHT) SDN BULAY 2 - Wahyuni, Sri (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
ABSTRACT This study aims to increase student learning activity in the fifth grade science content at SDN Bulay 2 by applying the Numbered Head Together (NHT) cooperative model. This research uses qualitative research methods, where the research design uses Kurt Lewin's research design which includes 4 stages, namely planning, action, observation, and reflection. This research was conducted at SDN Bulay 2 in class V with a total of 23 students consisting of 9 male students and 14 female students. Data collection techniques and instruments in this study used observation sheets, evaluation sheets, and documentation instruments. The results of the study using the Numbered Head Together (NHT) cooperative model, it can be seen that student learning activity increases, in cycle 1 the score is 1,955, with an average score of 85, completeness value is 82.60, and in cycle 2, it is increased with a score of total 2,155, with an average value of 93.69, completeness score of 100.